Controlling pythium root rot by nano-particle extracts from cordyceps and herbs - Phikul Intaparn (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Surveys of root and stem rot disease of Catharanthus roseus and collection of soil and diseased plant samples were conducted in a C. roseus nursery in Chiang Mai province. Isolation of the causal pathogen was made during November 2017 to September 2018 and 56 isolates of pathogens were obtained. The fungal isolates were proved to be pathogenic causing root rot of C. roseus by the detached leaf method and were used in a seedling inoculation test. The pathogen isolate MCRC-P05 gave the significantly highest virulence when compared to the other isolates and was followed in virulence by the isolate MCRC-P21. The pathogens were studied by morphological and molecular analysis. The pathogen isolates MCRC-P05 and MCRC-P21 were confirmed to be Pythium deliense and Phytopythium sp. by molecular analysis based on the internal transcribed spacer (ITS)-rDNA sequence. Then, the fungal sequences were aligned and they clustered with sequences obtained from the GenBank (NCBI) using a computer program. Therefore, Py. delicense and Phytopythium sp. were identified in this first report as causing C. roseus root rot in Chiang Mai province. In addition, the agrochemicals test showed various results in controling Py. deliense MCRC-P05 and Phytopythium sp. MCRC-P21. At the recommended concentration, fosetyl-aluminium and metalaxyl produced inhibition. Furthermore, propineb, thiram, phosphorous acid and tridemorph inhibited the growth of Py. deliense MCRC-P05 by more than 80%, while mancozeb inhibition was lower than 80%. Py. deliense MCRC-P05 was resistent to dimethomorph and Phytopythium sp. MCRC-P21 was resistent to thiram, dimethomorph and phosphorous acid. However, mancozeb, propineb, fosetyl-aluminium and tridemorph showed 100% inhibition of growth of Phytopythium sp. MCRC-P21 and metalaxyl resulted more than 80% inhibition of growth on Phytopythium sp. MCRC-P21. Cordyceps and two herbs of potential fungicide interest were extracted with three different solvents – ethanol, hexane fraction, and ethyl acetate and ethanol. The crude extracts were tested for inhibition of growth of the Py. deliense MCRC-P05, using the poison medium technique. The results showed that the ethyl acetate fraction extract of Vernonia amygdalina was best on growth inhibition of the pathogen; at 1,000 and 500 μg/ml it could inhibit 100 % and at 100, 50 and 10 μg/ml it inhibited the mycelial growth of the pathogen by 32, 16 and 13 %, respectively, with an ED 50 =107.08 μg/ml. All extracts of V. amygdalina showed antioxidant activities, and the ethyl acetate fraction extract showed the highest DPPH, ABTS and FRAP radical scavenging activities. The efficiency test of the crude extract on Pythium blight disease of C. roseus, used the detached leaf technique with a culture disc of the pathogen used for inoculation. The leaves had been treated with the extracts prior to inoculation. Results showed that the most effective growth inhibition (higher than 90 % at 500 μg/ml) was shown by the ethyl acetate fraction extracts. Nano-particles derived from V. amygdalina fraction extracts were tested for growth inhibition of the pathogen, using the poison medium technique. It was found that nano-particles exhibited significant antifungal activity against Py. deliense MCRC-P05 with an ED50 = 0.01 μg/ml. These effective fraction extracts were formulated as botanically derived fungicides and then evaluated in 2-month-old C. roseus plants inoculated with the pathogen MCRC-P05 and maintained in a greenhouse. The test plants grown in pots were treated with the ethyl acetate fraction extract, nano-particles and a standard chemical fungicide, metalaxyl, by applying the treatments into the soil in planting pots. Five days after treatment, the C. roseus plants treated with nano-particles and metalaxyl showed reduced disease severity, while all the plants in control treatment showed severe infection and died. This research finding is the first report using these plant extract as biofungicides to control C. roseus root rot caused by Py. deliense in Thailand.